Factors Associated with Low Sexual Desire in 45-Year-Old Men: Findings from the German Male Sex-Study. Issue 7 (10th June 2019) - Meissner, Valentin H.; Schroeter, Lukas; Köhn, Frank-Michael; Kron, Martina; Zitzmann, Michael; Arsov, Christian; Imkamp, Florian; Hadaschik, Boris; Gschwend, Jürgen E.; Herkommer, Kathleen
Abstract: Introduction: Although low sexual desire is 1 of the most common sexual dysfunctions in men, there is a lack of studies investigating associated factors in large, population-based samples of middle-aged men. Aim: To survey the prevalence of low sexual desire in a population-based sample of 45-year-old German men and to evaluate associations with a broad set of factors. Methods: Data were collected between April 2014–April 2016 within the German Male Sex-Study. Participants were asked to fill out questionnaires about 6 sociodemographic, 5 lifestyle, and 8 psychosocial factors, as well as 6 comorbidities and 4 factors of sexual behavior. Simple and multiple logistic regressions were used to assess potential explanatory factors. Main Outcome Measures: We found a notable prevalence of low sexual desire in middle-aged men and detected associations with various factors. Results: 12, 646 men were included in the analysis, and prevalence of low sexual desire was 4.7%. In the multiple logistic regression with backward elimination, 8 of 29 factors were left in the final model. Men having ≥2 children, higher frequency of solo-masturbation, perceived importance of sexuality, and higher sexual self-esteem were less likely to have low sexual desire. Premature ejaculation, erectile dysfunction, and lower urinary tract symptoms were associated with low sexual desire. Clinical Implications: Low sexual desire is common in middle-aged men, and associating factors that can potentially be modified should be considered during assessment and treatment of sexual desire disorders. Strengths & Limitations: The strength of our study is the large, population-based sample of middle-aged men and the broad set of assessed factors. However, because of being part of a prostate cancer screening trial, a recruiting bias is arguable. Conclusion: Our study revealed that low sexual desire among 45-year-old men is a common sexual dysfunction, with a prevalence of nearly 5% and might be affected by various factors, including sociodemographic and lifestyle factors, as well as comorbidities and sexual behavior.